The Construction of Consumerism Through Television Advertisements in the Film Joy (2015) (Cinematology: Journal Anthology of Film and Television Studies, 2024)
Film is one of the products of popular culture that is quite attached to society. In its popularity, Joy (2015) is one of the films that highlights explicitly or implicitly on how television as a mass media can construct people's consumptive behavior through the advertisements. Undeniable, popular culture is closely related to consumerism which is characterized by a sense of continuous dissatisfaction and consumption based not on needs, but desires or prestige. Currently, advertising in the media plays an important role in shaping the habitus of consumptive society and also as a medium of promoting commodities. This article studies the construction of consumerism through advertisements on television in the film Joy (2015) using qualitative methods. There are several stages of the research, namely observation, data collection in the form of verbal and non-verbal signs in the film, data analysis, and data presentation. The results of this study indicate that in the film, the representation of consumerism can be seen in people's enthusiasm for new commodities, which can be seen in the high sales figures, and consumers who buy commodities at high prices based on trends and desires. In this film, commodity advertising on television greatly affects consumers. However, consumers also play an important role in constructing consumerism through advertisements on television.